Analysis Of The Role Psychology in Emotion Control, Concentration, Confidence in the National Football Team in the 2023 Sea Games Final - Zulpikar Ilham; Sulaiman Sulaiman; Oktiia Woro; Hengki Kumbara (International Conference on Science, Education, and Technology, 2023)
The Garuda Muda Indonesia national football team has succeeded in ending the fast of winning a title in a 32-year wait to win a gold medal in the 2023 SEA Games football sport, the gold medals won at the championships of the Asean countries, the 2023 SEA Games are so very special and historical for the Garuda Muda Indonesia national football team and the Indonesian nation. The purpose of this study was to see how mental maturity competed for the U-22 Indonesian Garuda Young National Team through the results of good psychology during the match in the 2023 SEA Games final which took place at Cambodia Olympic Stadium, Phnom Penh. This research was conducted using a descriptive research approach to describe certain phenomena that occur in the mental psychology of the struggle of the U-22 Garuda Muda Indonesia National Team in the 2023 SEA Games final. The method used in this research is a qualitative method to examine the conditions of natural objects, where the researcher is a key instrument. Data was taken through observation and interviews using a Likert scale questionnaire and data analysis was carried out by descriptive analysis. The results showed that in the struggle of the Garuda Muda Indonesia national football team to win gold at the 2023 SEA Games event. Based on field research, the influence of psychological factors on the U-22 Garuda Muda football national team was clearly seen during the final match against the Thai national football team. It was concluded from the research results, that in general based on research results and discussion. Motivation, concentration, focus, confidence, emotional management and good match mentality are the main keys that make the U-22 Garuda Youth Football Team play brilliantly in the final..